Improving Food Security and Sustainability in Koperasi Merah Putih: A Conceptual Model of Food Supply Chain Management - Retno Widyani; Nuri Kartini; Andri Hermawan; Mhod Razif Idris (Jurnal Improsci, 2026)
Background. Food security and sustainability are key challenges in the modern food system, characterized by fragmented production, high food losses, and weak coordination among supply chain actors. Food Supply Chain Management (FSCM) is a strategic approach to integrating the flow of products, information, and logistics from upstream to downstream. Aims. This study aims to develop a conceptual model of FSCM based on Koperasi Merah Putih, the primary institutional actor in strengthening the food supply chain. Methods. The research method employed a systematic literature review of relevant scientific publications and policy documents. Result. The study results indicate that the Koperasi Merah Putih has the potential to act as a supply chain coordinator through production aggregation, logistics management, and information management. Information technology support, government policies, and logistics infrastructure strengthen the cooperative's ability to improve FSCM performance. Conclusion. Optimal FSCM performance subsequently contributes to increased food security and the sustainability of the food system. Implementation. The developed conceptual model is expected to serve as a basis for further empirical research and a reference for formulating cooperative-based food policies.